Solve the system by elimination

Algebra
Tutor: None Selected Time limit: 1 Day

{-2x + 2y + 3z = 0

{-2x - y + z = -3

{2x + 3y + 3z = 5

Oct 6th, 2015

Thank you for the opportunity to help you with your question!

first add the first and third equation

-2x + 2y + 3z = 0   +

2x + 3y + 3z = 5


so, 0 + 5 y + 6z =5.................(1)


now add the second and third equation

-2x - y + z = -3

2x + 3y + 3z = 5

so, 0 + 2y +4z = 2........................(2)


0 + 2y +4z = 2  multiply by 3

     6y +12y = 6.....................(3)


0 + 5 y + 6z =5.................(1)  multiply by 2

   10 y + 12y =10..............(4)


now subtract (3) from (4)

   10 y + 12y =10   - 

      6y +12y = 6


so,  4 y + 0 = 4

       4y = 4

         y =1


now substitute y =1 in  5 y + 6z =5.................(1)

                                     5*1 + 6z =5

                                              6z =5-5

                                               z = 0


-2x + 2y + 3z = 0

substitue value of y=1 and z=0

-2x + 2*1 + 3*0 = 0

-2x    =  -2

  x =1



ANSWER is

x =1

y =1

z = 0



hope you understood..please message if you have any doubts...thank you
Oct 6th, 2015

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Oct 6th, 2015
...
Oct 6th, 2015
Feb 23rd, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer